Recent Advances in Plant Biotechnology 2009
DOI: 10.1007/978-1-4419-0194-1_9
|View full text |Cite
|
Sign up to set email alerts
|

Plants as Sources of Energy

Abstract: This chapter is concerned with biotechnological applications involving the use of plants as sources of energy. Plants contain stored carbon captured from light-catalyzed carbon dioxide fixation via photosynthesis. This stored carbon from plants is available in oil and coal deposits that can be used as energy sources known as petrofuels. Living plants or plant residues can be used to generate biofuels such as methane from methane generators, wood fuel from wood chips, and alcohol from plant-based starch or cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Apart from the extracts, the elephant grass bagasse can be used as feedstock for the production of cellulosic ethanol. Lignocellulosic biomass has been reported to contain 30-60% cellulose, 20-40% hemicelluloses and 10-30% lignin [87,89]. Grasses generally have 25-40% cellulose, 25-50% hemicelluloses and 10-30% lignin [89].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the extracts, the elephant grass bagasse can be used as feedstock for the production of cellulosic ethanol. Lignocellulosic biomass has been reported to contain 30-60% cellulose, 20-40% hemicelluloses and 10-30% lignin [87,89]. Grasses generally have 25-40% cellulose, 25-50% hemicelluloses and 10-30% lignin [89].…”
Section: Resultsmentioning
confidence: 99%
“…Lignocellulosic biomass has been reported to contain 30-60% cellulose, 20-40% hemicelluloses and 10-30% lignin [87,89]. Grasses generally have 25-40% cellulose, 25-50% hemicelluloses and 10-30% lignin [89]. De Morais et al [28] reported 27.9-28.2% cellulose, 11.9-12.4% lignin and 2.2-2.6% ash for elephant grass bagasse.…”
Section: Resultsmentioning
confidence: 99%
“…Lignocellulosic biomass has gained increasing research interest because of its renewable nature [ 32 ]. Lignocellulosic biomass refers to both non-woody and wood biomass, which differ in their chemical and physical composition [ 33 ]. Holocellulose (a mixture of hemicellulose and cellulose) and lignin make up the category of lignocellulosic biomass.…”
Section: Flammability Of Biocompositesmentioning
confidence: 99%
“…Energy crop plants are grown specifically for biofuel production, but the crops vary with geography (Koçar and Civaş, 2013; Hood et al ., 2013). For example, in the United States, the most cultivated energy crop plants are corn, soybeans, willows and switchgrass (Cseke et al ., 2009); while in northern Europe preferential crops are rapeseed, wheat, sugar beet and willows. Sugarcane is the main energy crop grown in Brazil with sugar being fermented and bagasse burnt in combined cycle plants.…”
Section: Introductionmentioning
confidence: 99%